Sudden cardiac death after acute decompensation in heart failure patients: implications of discharge haemoglobin levels. (29th July 2021) - Fukuoka, Ryoma; Kohsaka, Shun; Shiraishi, Yasuyuki; Sawano, Mitsuaki; Abe, Takayuki; Levy, Wayne C.; Nagatomo, Yuji; Nishihata, Yosuke; Goda, Ayumi; Kohno, Takashi; Kawamura, Akio; Fukuda, Keiichi; et al.
Abstract: Aims: Heart failure (HF) patients have a high risk of mortality due to sudden cardiac death (SCD) and non‐SCD, including pump failure death (PFD). Anaemia predicts more severe symptomatic burden and higher morbidity, as noted by markedly increased hospitalizations and readmission rates, and mortality, underscoring its importance in HF management. Herein, we aimed to determine whether haemoglobin (Hb) level at discharge affects the mode of death and influences SCD risk prediction. Methods: We evaluated the data of 3020 consecutive acute HF patients from a Japanese prospective multicentre registry. Patients were divided into four groups based on discharge Hb levels. SCD was defined as an unexpected and otherwise unexplained death in a previously stable patient or death due to documented or presumed cardiac arrhythmia without a clear non‐cardiovascular cause. The mode of death (SCD, PFD or other cause) was adjudicated by a central committee. Finally, we investigated whether adding Hb level to the Seattle Proportional Risk Model (SPRM; established risk score utilized to estimate 'proportion' of SCD among death events) would affect its performance. Results: The mean age of studied patients was 74.3 ± 12.9 years, and 59.8% were male. The mean Hb level was 12.0 ± 2.1 g/dL (61.3% of patients had anaemia defined by World Health Organization criteria). During the 2‐year follow‐up, 474 deaths (15.7%) occurred, including 93 SCDs (3.1%), 171 PFDs (5.7%) and 210 other deaths (7.0%; predominantly non‐cardiac death). Absolute risk of PFD ( P  < 0.001) or other death ( P  < 0.001) increased along with the severity of anaemia, whereas the incidence of SCD was low but remained consistent across all four groups ( P  = 0.440). As a proportion of total deaths in each Hb level group, the contributions from non‐SCD increased and from SCD decreased along with anaemia severity ( P  = 0.007). Adding Hb level to the SPRM improved the overall discrimination (c‐index: 0.62 [95% confidence interval (CI) 0.56–0.69] to 0.65 [95% CI 0.59–0.71]), regardless of the baseline ejection fraction (EF) (c‐index: 0.64 [95% CI 0.55–0.73] to 0.67 [95% CI 0.58–0.75] for reduced EF and 0.55 [95% CI 0.45–0.66] to 0.61 [95% CI 0.52–0.70] for preserved EF). Conclusions: The discharge Hb level provides information about both absolute and proportional risks for each mode of death in acute HF patients, and the addition of Hb level improves the performance of SPRM by identifying more non‐SCD cases. Future 'proportional' SCD risk models should incorporate Hb level as a covariate to meet this high performance.